Foreign Exchange Forecasting by using Artificial Neural Networks: A Survey of Literature - Ardiansyah, Soleh; Mazlina, Abdul Majid; Jasni, Mohamad Zain (2012)
Foreign exchange (Forex) is the global scale trading of currency and the most liquid financial market. Therefore, predicting Forex has been challenged for many years. On the other hand, Artificial Neural Network (ANN) was widely used by researchers as a prediction technique since it can provide the best prediction result. This paper surveys recent literature in the domain of ANN which used to forecast foreign exchange. This paper classifies the literature based on forecasting model, input data type, forecasting intervals, and evaluation method. This paper reveals progressive applications in addition to existing gap and less considered area and determines the future work of researchers.